2007
DOI: 10.1149/1.2712134
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Micrometer-Sized Thin Films of Electrocoated Carbazole with p-Tolylsulfonyl Pyrrole on Carbon Fiber Microelectrodes

Abstract: Carbazole ͑Cz͒ monomers with p-tolylsulfonyl pyrrole ͑pTsp͒ ͑used as self-dopant͒ were electrochemically coated onto micrometer-sized carbon fiber by potentiodynamic method. The resulting micrometer-sized thin films of homopolymer and copolymers were characterized by using electrochemical methods ͑i.e., cyclic voltammetry͒, solid-state conductivity measurements ͑four-point probe͒, spectrophotometric methods ͑in situ spectroelectrochemistry͒, Fourier transform infrared reflectance spectroscopy, and scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…A promising solvent for preparing PCz by electropolymerization should allow both carbazole and the supporting electrolytes to dissolve in a large quantity. PCz films are thus frequently prepared in volatile organic solvents such as CH 3 CN and CH 2 Cl 2 with LiClO 4 and tetraalkylammonium salts usually employed as the supporting electrolytes [14,15,[20][21][22]. However, many previous studies have indicated that the quality of PCz films obtained in such electrolytes was poor, usually in the form of powders.…”
Section: Introductionmentioning
confidence: 99%
“…A promising solvent for preparing PCz by electropolymerization should allow both carbazole and the supporting electrolytes to dissolve in a large quantity. PCz films are thus frequently prepared in volatile organic solvents such as CH 3 CN and CH 2 Cl 2 with LiClO 4 and tetraalkylammonium salts usually employed as the supporting electrolytes [14,15,[20][21][22]. However, many previous studies have indicated that the quality of PCz films obtained in such electrolytes was poor, usually in the form of powders.…”
Section: Introductionmentioning
confidence: 99%
“…The bands at 912 and 771 cm -1 were attributed to the =C-H in-plane vibration and out-of-plane vibration, respectively [62]. The strong absorption bands at 1086 cm -1 indicate that poly(PPA) film is highly doped with the anion of ClO 4 - [63]. GNPs/NiO/poly(PPA)-Ty and GNPs/ poly(PPA)-Ty samples showed new peaks around 1710-1590 and 1510-1490 cm -1 , which is characteristic of the -C=O stretching of amide I and the N-H bending of amide II for the -CO-NH-bond formed between the enzyme and polymer, respectively (Figure 8c) [64].…”
Section: Interfacial Properties Ofmentioning
confidence: 98%
“…The separation between the anodic and cathodic peaks is associated with the ion transport resistance involved in these redox reactions [28,29]. Therefore, the difference between anodic and cathodic peaks (DE) can serve as an indication for resistance of ion migration in the electrode [30].…”
Section: Electrocopolymerization Of Thczhamentioning
confidence: 99%